Pengaruh Level Pupuk Organik Cair Daun Kelor terhadap Produksi Rumput Gajah Mini pada Tanah Latosol: The Effect of Liquid Organic Fertilizer Level of Moringa Leaves on Mini Elephant Grass Production in Latosol Soil - Defri Debora Lenci Missa; Domingus Benyamin Osa; Edi Djoko Sulistijo (Universitas Nusa Cendana, 2023)
The research aimed at examining the effect of doses of liquid organic fertilizer on Moringa leaves (Moringa oleifera) on the production of mini elephant grass (Pennisetum purpureum cv. Mott) on latosol soil, was conducted in Kayu Putih Village, Oebobo District, Kupang City for 3 months. This study was designed based on a completely randomized design with four treatments and four replications. The four treatments were: M0: without Moringa liquid fertilizer (control), M1: 100 ml Moringa liquid fertilizer, M2: 200 ml Moringa liquid fertilizer, M3: 300 ml Moringa liquid fertilizer. The parameters observed were the production of fresh, dry and organic matter. The results of the analysis of variance showed that the treatment had no significant effect (P>0.05) on mini elephant grass production. It was concluded that the application of 100 ml of liquid organic fertilizer for Moringa leaves tended to give better results on the production of mini elephant grass on latosol soil. Penelitian yang bertujuan untuk mengkaji pengaruh level dosis pupuk organik cair daun kelor (Moringa oleifera) terhadap produksi rumput gajah mini (Pennisetum purpureum cv. Mott) pada tanah latosol, telah dilakukan di Kelurahan Kayu Putih, Kecamatan Oebobo, Kota Kupang selama 3 bulan. Penelitian ini didesain berdasarkan rancangan acak lengkap dengan empat perlakuan dan empat ulangan. Ke empat perlakuan adalah: M0: tanpa pupuk cair daun kelor (kontrol), M1: 100 ml pupuk cair daun kelor, M2: 200 ml pupuk cair daun kelor, M3: 300 ml pupuk cair daun kelor. Parameter yang diamati adalah produksi bahan segar, bahan kering dan bahan organik. Hasil analisis ragam menunjukkan bahwa perlakuan berpengaruh tidak nyata (P>0,05) terhadap produksi rumput gajah mini. Disimpulkan bahwa pemberian 100 ml pupuk organik cair daun kelor cenderung memberikan hasil yang lebih baik terhadap produksi rumput gajah mini pada tanah latosol.